Myostatin inhibits insulin‐like growth factor 1–dependent citrate secretion and osteogenesis via nicotinamide adenine dinucleotide phosphate oxidase‐4 in a mouse mesenchymal stem cell line. Issue 1 (7th September 2022) - Liu, Xin‐Hua; Pan, Jiang Ping; Bauman, William A.; Cardozo, Christopher
Abstract: Citrate is an indispensable component of bone. Reduced levels of citrate in bone and serum are reported in the elderly and in osteoporosis patients. Myostatin (Mstn) is implicated in skeletal homeostasis, but its effects on osteogenesis remain incompletely understood. Nox4 has critical roles in bone homeostasis. TGF‐β/Mstn‐associated Smad2/3 signaling has been linked to Nox4 expression. Insulin‐like growth factor (IGF‐1) has been shown to counteract many regulatory effects of Mstn. However, the crosstalk among Mstn, IGF‐1, and Nox4 is not well understood; the interactive effects of those factors on citrate secretion, osteogenic differentiation, and bone remodeling remain unclear. In this study, we demonstrated that osteogenic differentiation induced an IGF‐1–dependent upregulation of citrate secretion that was suppressed by Mstn. Inhibition of Nox4 prevented Mstn‐induced reduction of citrate secretion. In addition, Mstn reduced bone nodule formation; these changes were prevented by Nox4 inhibition. Moreover, Mstn increased the ratio of RANKL to OPG mRNAs to favor osteoclast activation. These results indicate that Mstn negatively regulates osteogenesis by increasing levels of Nox4, which reduced IGF‐1 expression, citrate secretion, and bone mineralization while also altering the RANKL to OPG ratio. These findings provide new and highly relevant insights into the osseous effects of myostatin. Abstract : Citrate is an indispensable component of bone. Myostatin (Mstn) is implicated in skeletal homeostasis, but its effects on osteogenesis remain incompletely understood. Nox4 has critical roles in bone homeostasis. TGFβ/Mstn‐associated Smad2/3 signaling has been linked to Nox4 expression. IGF‐1 has been shown to counteract many regulatory effects of Mstn. In this study, we studied the crosstalk among Mstn, IGF‐1, and Nox4, and the interactive effects of those factors on citrate secretion, osteogenic differentiation, and bone remodeling.